ChemInform Abstract: Pd/Mannose Promoted Tandem Cross Coupling‐Nitro Reduction: Expedient Synthesis of Aminobiphenyls and Aminostilbenes. Issue 35 (September 2015) - Rohilla, Sandeep; Pant, Pradeep; Jain, Nidhi
Abstract The dual role of D‐mannose as ligand for the Pd‐catalyzed cross‐coupling and as hydrogen source for the nitro reduction is demonstrated.